Genetic counseling for hereditary cancer syndromes: a 5-year experience from a single center in Bulgaria - Mari Hachmeriyan; Mari Hachmeriyan; Mariya Levkova; Mariya Levkova; Dinnar Yahya; Dinnar Yahya; Milena Stoyanova; Milena Stoyanova; Eleonora Dimitrova (Oncology Reviews, 2025)
This study presents a 5-year retrospective analysis of genetic counseling (GC) services for hereditary cancer syndromes (HCS) at a single center in Bulgaria. The aim is to describe the demographic and epidemiological characteristics of patients seeking GC, the uptake of genetic testing, and the spectrum of identified pathogenic variants. The results highlight an increasing trend in GC utilization. Key findings include differences in patient profiles between those seeking general HCS assessment and those undergoing tumor biomarker testing, the impact of financial accessibility on genetic testing uptake, and a pathogenic variant detection rate of 28% in tested individuals. The most frequently identified conditions were Hereditary Breast and Ovarian Cancer Syndrome and Lynch Syndrome, with pathogenic variants detected in genes such as BRCA1, MSH2, PALB2, and STK11. These findings underscore the need for enhanced awareness, improved financial access to testing, and the establishment of systematic cascade screening programs in Bulgaria.